PRINSIP AKUNTANSI SYARIAH PADA LEMBAGA KEUANGAN MIKRO SYARIAH DI INDONESIA - Ratih, Dewi; Latifah, Eny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Islamic accounting principles play an important role in the operations of Islamic microfinance institutions in Indonesia. This study explores the application of Islamic accounting principles in the context of Islamic microfinance institutions. These principles include joint ownership, profit and loss sharing, avoidance of speculative practices and prohibition of usury. Islamic accounting principles in Islamic microfinance institutions are based on Islamic teachings, which means that Islamic microfinance institutions are required to carry out practices in accordance with Islamic values. This study provides an understanding of these principles in maintaining conformity with sharia principles. It analyzes the impact of the implementation of Islamic accounting principles on transparency, customer trust, financial management, financial reporting and sustainability of Islamic microfinance. The research also identifies a number of challenges faced in the implementation of Islamic accounting principles such as the shortage of trained human resources.